Application and performance assessment of a Reflux Classifier for iron ore particle classification - Zhiyuan Zhang; Mengqi Ma; Lingfeng Xiang; Yanfeng Li (Minerals Engineering, 2026)

Effect of sodium hexametaphosphate on the flotation separation of biotite and K-feldspar in the NaOL/DDA system - Xingyu Hu; Bo Mei; Lingfeng Shen; Wei Sun; Yanxiu Wang; Jinghua Huang; Li Wang (Minerals Engineering, 2026)

Src interacts with TRAF5 and promotes NF-κB-associated antiviral responses against iridovirus in marine teleost - Lingfeng Guan; Yi Li; Ting Yu; Jiamei Long; Runchang Zhou; Zhifeng Chen; Hua Huang; Jinglin Tan; Min Yang; Shaowen Wang; Qiwei Qin (Fish & Shellfish Immunology, 2026)

Distinct soil microbial community composition and structure: evidence from soil inside and outside the cattle farm - Qi Ding; Jiayi Li; Fengling Xue; Wenjun Cui; Shiguang Hu; Lingfeng Yu; Wanyue Huang; Lin Li; Ping Cheng (Brazilian Journal of Microbiology, 2026)

Selective flotation of lepidolite from albite and quartz using a Hyperbranched surfactant THQ-8: Insights through foam property and adsorption behavior - Yukun Wu; Lingfeng Shen; Rui Xu; Ning Sun; Li Wang (Minerals Engineering, 2026)

Long-term bending performance degradation of GFRP bar-seawater sea sand concrete beams in marine environments: from material degradation to component response and bearing capacity model correction - Guanghao Mai; Zhe Xiong; Haoran Zhou; Lingfeng Zhou; Xiaohui Li; Feng Liu; Lijuan Li (Engineering Structures, 2026)

Wearable triboelectric sensor based on a single-line-contact electrode architecture for gesture recognition and human–machine interaction - Long Li; Jingyun Dai; Jiayang Lyu; Yifan Shen; Yanmin Guo; Lingfeng Du; Zhiqian Wei; Xiongtu Zhou; Yongai Zhang; Hyung-Soon Kim; Dianlun Li; Kun Wang; et al. (Chemical Engineering Journal, 2026)

Flotation of quartz from albite using oligomeric surfactant THQ-8 in synergy with NaOL - Yukun Wu; Lingfeng Shen; Rui Xu; Ning Sun; Li Wang (Minerals Engineering, 2026)

Advancing analysis of biofuel precursors from lignin: complete molecular characterization using GC × GC-FID - Linyu Zhu; Miloš Auersvald; Cunhao Cui; Yuhe Liao; Jing Zhang; Qing He; Lingfeng Li; Yi Ouyang; Zhongyue Zhou; Fei Qi; Kevin M. Van Geem (Fuel, 2026)

Topology-engineered hydrogel with cellulose nanosheets for robust and high-capacity zinc-ion batteries - Wenxuan Lei; Heng Huang; Wenyu Liu; Lingfeng Zhou; Guoping Li; Pan Chen; Zu Chang; Jiangfeng Qian; Ang Lu (Carbohydrate Polymers, 2026)

Multi-objective optimization of ship resistance and seakeeping using an improved Voronoi-based parallel sequential sampling method - Dongqin Li; Yu Zhang; Yanqing Yin; Wenwen Chen; Bohan Wang; Zishuai Wang; Lingfeng Lu (Ocean Engineering, 2026)

Reverse flotation desilication of bauxite Ore: unraveling the mechanism of Cu(II)-SDSo in selective separation of kaolinite from diaspore - Boai Zhang; Lingfeng Shen; Honghu Tang; Jianjun Wang; Wei Sun; Jianyong He; Li Wang (Minerals Engineering, 2026)

Intensive mariculture promotes molecular reorganization of dissolved organic matter in coastal waters - Kai Shen; Niangming Duan; Zhibing Jiang; Jiang Shen; Haibo Jiang; Hailong Huang; Lingfeng Zhou; Dongping Shi; Mei Li; Ying Kang; Yuanhao Wang; Xubiao Yu (Environmental Research, 2026)

Strongly coordinating anions and cosolvent synergy enabled lithium metal batteries - Yutao Liu; Yi Li; LingFeng Zhang; Mengmeng Tan; QiXian Zhang; Wei Lü (Chemical Engineering Journal, 2026)

Precursor-engineered lignin-derived Co/N-doped carbon for high-efficiency electrocatalytic HMF oxidation: The critical role of pretreatment history - Chenxin Jin; Yajun Liu; Lingfeng Li; Yihan Wang; Changzhou Chen; Jianchun Jiang (Biomass and Bioenergy, 2026)

Synergistic co-assembly of phytic acid and pluronic F127 for environmentally benign, mechanically robust, and fire-resistant silica xerogel monoliths - Chengdong Li; Lingfeng Li (Chemical Engineering Journal, 2026)

Effects of Salinity on Growth, Survival, Gonadal Development, and Immune-System Indicators of Crassostrea ariakensis - Xiaotong Li; Xue Zhang; Zhaoqi Liu; Lingfeng Kong (Journal of Ocean University of China, 2026)

Cross–Spectrum–Based Shallow Water Retrieval Using High–Resolution C–Band Miniaturized SAR Satellites - Lingfeng Zhou; Quankun Li; Liangsheng Li; Xupu Geng; Xiao-Hai Yan (Journal of Marine Science and Engineering, 2026)
Topographic and geomorphic information provides an essential basis for human development and utilization of natural resources, disaster prevention and mitigation, ecological environment protection, and scientific research. Among spaceborne remote sensing approaches, Synthetic Aperture Radar (SAR) stands out due to its ability to actively transmit and receive microwave signals, enabling high spatial coverage, all–weather, and all–day observation. With the rapid development of miniaturized satellite constellations, high–revisit and high–resolution SAR data have become more accessible, offering unprecedented opportunities for dynamic ocean observation. However, existing SAR–based bathymetry methods based on power–spectrum analysis are susceptible to sea–spike noise and 180° directional ambiguity, limiting their accuracy in shallow coastal waters. To address these limitations, a Cross–Spectrum–based Wave Ray Tracking bathymetry retrieval algorithm (CS–WRT) is developed using high–resolution imagery from mini–SAR constellations including HiSea–1 and Chaohu–1. The method incorporates cross–spectrum analysis into a localized wave ray tracking framework to effectively suppress sea–spike noise and accurately extract shallow–water wave vectors. Applied to six SAR images over the Taiwan Strait, CS–WRT consistently outperformed the power–spectrum approach in coastal environments. In the Jinjiang coastal region, comparison with Electronic Navigational Chart (ENC) data yielded a root mean square error of 2.22 m, a mean absolute percentage error of 7.06%, and a Pearson correlation coefficient of 0.84. Analysis of the shoaling slope parameter k further revealed that stronger wave shoaling effects correlate with improved retrieval accuracy, suggesting its potential as a diagnostic indicator of retrieval reliability.

Mechanisms of interlayer force transmission and slip surface penetration in pile-reinforced reservoir landslides with multi-sliding zones - Haojie Duan; Zongxing Zou; Yang Zhang; Lingfeng Wu; Jiang Li; Jianqiang Tao; Yikai Niu; Xinli Hu (Landslides, 2026)

Dynamic characterization of representative naval steels under high-velocity fragment impact and functional vulnerability assessment of naval propulsion-system components - WenCai Sun; HouXiang Wang; LingFeng Hu; YuAng Shi; JianNan Li; ZiChun Yang (Ocean Engineering, 2026)

Simple and large-scale preparation of HPAMAM/PVA sponge with robust mechanical properties for hexavalent chromium adsorption - Ji Gao; Li Cai; Lingfeng Zhang; Cunwei Fan; Hao Zhang; Jie Sun; Kai Guo (Journal of Environmental Chemical Engineering, 2026)

Modelling and operation performance of the hybrid borehole heat exchangers constituted of a shallow U-pipe array and medium-deep coaxial pipe - Shilong Yang; Yaru Li; Lingfeng Huang; Qingbo Yang; Ke Zhu; Yudong Mao; Wenke Zhang; Mingzhi Yu (Energy and Buildings, 2026)

Co-exposure to polystyrene microplastics and perfluorooctanoic acid can exacerbate lipid metabolism disorders and liver damage in adult zebrafish - Sijie Tian; Ruixiang Li; Ya Zeng; Lingfeng Qin; Caicheng Long; Taiping Qing; Peng Zhang; Bo Feng (Journal of Environmental Sciences, 2026)

Dietary 5-aminolevulinic acid induces strain-specific effects on shell color and innate immunity in Pacific oyster (Crassostrea gigas) through divergent porphyrin metabolism - Biyang Hu; Hong Yu; Chengxun Xu; Lingfeng Kong; Shikai Liu; Shaojun Du; Qi Li (Fish & Shellfish Immunology, 2026)

Partially etched Ti2AlN/Ti2N/TiN ternary composite as a synergistic catalyst for enhanced hydrogen storage kinetics and cycling stability of NaAlH4 - Chen Jin; Lingfeng Wang; Zhenke Chen; Hang Che; Shuzhong Wang; Zhiheng Liu; Tao Chen; Li Wang; Yuyuan Zhao; Xinhua Wang; Haoyuan Zheng; Haizhen Liu; et al. (Chemical Engineering Journal, 2026)

Nickel incorporation engineering for synergistic regulation of oxygen vacancies and electronic band configuration in Bi2O3 nanosheets for high-performance supercapacitor electrodes - Lingfeng Li; Weihao Zhang; Xuexuan Luo; Xueyi Chang; Muqing Chen; Zhiyu Cheng; Yongfu Qiu; Yu Wang (Chemical Engineering Journal, 2026)

Long-Term in situ Monitoring of Anchoring System and Preliminary Analysis of Monitoring Data - Luobin Zheng; Huiming Tang; Liangqing Wang; Changdong Li; Chengren Xiong; Zongxing Zou; Chenlu Wang; Lingfeng Zhu; Yifan Zhang (Journal of Earth Science, 2026)

Leaf Size Variation in Response to Climate Drivers Depends on Plant Life Form - Jiayi Lu; Shihao Wen; Siyu Chen; Yuran Dong; Xiuping Wu; Yao Li; Min Zhang; Zhiwei Ge; Jonathan M. Chase; Lingfeng Mao (Journal of Biogeography, 2026)
Aim Plant leaf size and shape vary across major climatic gradients, reflecting the mechanisms for how plants regulate the balance of carbon, water, and heat. However, the influence of climate on leaf traits can be confounded by multiple factors, and the complex variation among different plant groups remains insufficiently understood. Here, we investigated how climate influences leaf size traits and whether this effect is moderated by plant life form. Location China. Taxon Angiosperms. Methods Based on leaf length, width, and aspect ratio data from 26,726 angiosperm species distributed across major climate gradients in China, we analysed the effects of temperature and precipitation on leaf size traits, and compared differences among plant life forms (woody vs. herbaceous and evergreen vs. deciduous). Additionally, spatial heterogeneity was assessed across eight vegetation zones. Results Leaves are generally larger and rounder in warm and humid areas, and smaller and narrower in cooler and more arid areas. All leaf size traits respond more strongly to precipitation than temperature, with leaf length showing the strongest responses to both climate variables. Herbaceous and deciduous species exhibit stronger climate responses nationwide, whereas woody and evergreen species are more sensitive within vegetation zones. Key responsive traits show clear geographic shifts. Main Conclusions Overall, we find that leaf size and shape vary strongly across China, as a result of climate variation, but these patterns are modified by dominant regional ecological processes and the ecological strategies of plant life forms. These findings not only help clarify variation in plant traits along climatic gradients, but also provide a theoretical framework for predicting how different plant morphologies will respond to ongoing climate change.

ATP-citrate lyase is a critical regulator of physiological and pathological angiogenesis - Chong Xu; Ying Lin; Zeyu Wang; Cailin Feng; Lingfeng Luo; Shuai Guo; Han Zhang; Lu Liu; Azhen Fan; Penglong Qi; Dongyang Jiang; Yiming Xu; et al. (Angiogenesis, 2026)

Wheat density drives negative density dependence in nitrogen uptake and root plasticity in wheat–weed communities - Li Zhang; Weiqiang Liu; Yizhong Rong; Jiazhen Xi; Lingfeng Mao; Anna Gunina; Zhen Zhang (Rhizosphere, 2026)

Benzyl isothiocyanate inhibits the conjugative transfer of mcr-1-positive plasmid via suppressing intercellular contact and limiting energy supply - Ping Cheng; Shuying Liang; Shixin Gui; Xinyu Wang; Lingfeng Yu; Wenjun Cui; Chunxu Lu; Lin Li (Journal of Environmental Management, 2026)

A novel transformer-based CO2 retrieval framework incorporating prior constraint and hierarchical features injection: assessment of transferability for Tansat-2 - Lingfeng Zhang; Lu Zhang; Xingying Zhang; Tiantao Cheng; Xifeng Cao; Tongwen Li; Dongdong Liu; Yang Zhang; Yuhan Jiang; Ruohua Hu; Haiyang Dou; Lin Chen (ISPRS Journal of Photogrammetry and Remote Sensing, 2026)

The regulation of the environmental behavior of NPs by humic acid: A review - Xuelan Chen; Lingfeng Zhu; Hongtao Li; Sicheng Xiong (Environmental Research, 2026)

Multi-omics and neurophysiological insights into flavor enhancement of low-salt shrimp paste fermented by Bacillus velezensis BV-T11 - Kuan Lu; Haoen Li; Lingfeng Ji; Yuhan Zheng; Wancui Xie (Chemical Engineering Journal, 2026)

Synergistic CeH2.51/graphene nanointerface engineering for enhanced kinetics and cycling stability of Mg(NH2)2–2LiH - Chen Jin; Haoyuan Zheng; Lingfeng Wang; Zhenke Chen; Hang Che; Shuzhong Wang; Zhiheng Liu; Tao Chen; Li Wang; Yuyuan Zhao; Xinhua Wang; Haizhen Liu; et al. (Chemical Engineering Journal, 2026)

Octonions and 7-dimensional space vector transformation - Lingfeng Liang; Hanwei Zhang; Kezhao Li; Hua Zhang (Applied Geophysics, 2026)

Polyphthalocyanine-based nanostructure for sono-immunotherapy by reprogramming the tumor microenvironment and blocking immune checkpoint - Lingfeng Jiang; Jiawei Wang; Wenjun Liu; Xin Xie; Xiao Luo; Ling Tu; Liangqing Tang; Qing Zhang; Hongmei Yuan; Hanfeng Yang; Qi Li; Sujiao Cao; et al. (Chemical Engineering Journal, 2026)

Comparative Analysis Provides Insights into the Phylogeny of Chamidae (Bivalvia: Veneroida) Through a Mitogenomic Approach - Jing Li; Yu Wang; Tao Xu; Lingfeng Kong; Qi Li (Journal of Ocean University of China, 2026)

Reproductive capacity and hereditary impact of triploid Crassostrea gigas and its aneuploid progeny - Xianchao Bai; Hong Hu; Chengxun Xu; Lingfeng Kong; Hong Yu; Shikai Liu; Haijun Liu; Shaojun Du; Qi Li (Marine Life Science & Technology, 2026)

Orange-shell phenotype regulated by CgABCG2-mediated protoporphyrin IX transport in Pacific oyster (Crassostrea gigas) - Biyang Hu; Hong Yu; Lingfeng Kong; Shikai Liu; Qi Li (Aquaculture, 2026)

Parallel cooperative path following control for multiple cyber-physical MASSs based on DN-ESO - Lingfeng Li; Lu Liu; Bing Han; Bing Wu; Zhouhua Peng (Ocean Engineering, 2026)

Enhancement mechanism of metal ions on lepidolite flotation in mixed NaOL/DDA system - Rui Xu; Lingfeng Shen; Jinghua Huang; Honghu Tang; Haisheng Han; Wei Sun; Li Wang (Minerals Engineering, 2025)

Plasmid engineering reveals size-dependent effects of plastic particles on horizontal gene transfer via transformation in Escherichia coli: Critical roles of plasmid size and plastic particle-bacteria spatial configuration - Lingfeng Zhu; Xuelan Chen; Zhihao Zhao; Mingzhu Huang; Yuechen Zhu; Hongtao Li; Yanna Shao; Mengrong Wang; Sicheng Xiong; Baoshan Xing (Journal of Hazardous Materials, 2025)

Synthesis and performance evaluation of cobalt-histidine hybrid nanoflowers as efficient heterogeneous catalysts for peroxymonosulfate activation - Qianqian Zhao; Huiyao Li; Junxue Chen; Fangui Meng; Lingfeng Deng; Kun Du (Journal of Environmental Chemical Engineering, 2025)

Experimental and numerical study of a novel thin metal mesh infrared radiant burner - Jiarui Li; Tong Jiang; Lingfeng Dai; Hanlin Zhang; Chun Zou (Fuel, 2025)

A refined incremental homogenization approach for heterogeneous nonlinear geomaterials without isotropization - Yongdong Li; Yuanming Lai; Zhaomin Lv; Xinwen Wang; Yian Zhou; Zipeng Qin; Lingfeng Guo; Lunyang Zhao (Computers and Geotechnics, 2025)

Identifying divergence time and paleoclimate change hotspots for better conservation under future climate change - Yuheng Chen; Jonas J. Lembrechts; Yann Hautier; Dongfan Xu; Yao Li; Yuran Dong; Lingfeng Mao (Biological Conservation, 2025)

Protective role of sulforaphane in lipid metabolism-related diseases - Lingfeng Zhao; Jiahuan Li; Yiping Dang; David Fisher; Nguyen Thi Thu Hien; Erkin Musabaev; Khrystyna Pronyuk; Lei Zhao (Molecular Biology Reports, 2025)

Sex-Specific ORFs in Marine Clams (Bivalvia: Veneridae) with Doubly Uniparental Inheritance: Exploring Their Origin and Putative Function - Tao Xu; Lingfeng Kong; Qi Li (Marine Biotechnology, 2025)

In situ electrocatalytic nitrate-to-nitrite conversion-driven anammox in MBRs for extremely efficient ammonium-containing wastewater treatment - Lingfeng Ni; Peifang Wang; Gang Zhou; Zibin Li; Yayi Wang (Water Research, 2025)

Urban vegetation productivity under climate change and increasing urbanization: Insights from both urban-rural comparison and trend analysis for global cities - Jiuyi Chen; Bo Qiu; Weidong Guo; Xin Miao; Yipeng Cao; Zhihan Zhao; Siwen Zhao; Lingfeng Li; Yueyang Ni; Shihan Tang; Limei Yang (Urban Forestry & Urban Greening, 2025)

Devonian–Triassic tectonic evolution of the Western Qinling Orogenic Belt of central China: Insights from detrital zircon U Pb chronology and rock geochemistry - Yan Zhang; Shuang Dai; Futian Liu; Dongbao Guo; Lingfeng Qin; Zhongzhao Ding; Yongfa Chen; Xinnan Fang; Xiaojun Ma; Yu Wang; Hua Li (Palaeogeography, Palaeoclimatology, Palaeoecology, 2025)

Critical hydro-geomorphological characteristics related to lateral erosion–deposition difference within the multilevel bifurcation system of the Yangtze Estuary, China - Boyuan Zhu; Shiyu Zhang; Lingling Zhu; Lingfeng Liu; Wenjun Yu; Jinwu Tang; Yongzhou Cheng; Yitian Li; Alistair G.L. Borthwick (Journal of Hydrology, 2025)

Comparative analysis of machine learning based dissolved oxygen predictions in the Yellow River Basin: The role of diverse environmental predictors - Lingling Liu; Xiaoli Zhao; Lingfeng Zhou; Jiangtao Liu; Wenjing Li; Bolun Zhang; Junhong Ling; Fengchang Wu (Journal of Environmental Management, 2025)

Ultrasensitive SERS detection of cytokines through specific binding and multiple reporter molecules - Hairong Chen; Hengchang Zhang; Lingfeng Duan; Kaidi Sun; Rui Li; Yunxia Wang; Jiacheng Yao; Changchun Yan; Ying Liu; Ying Wu; Guohai Yang; Caiqin Han (Analytica Chimica Acta, 2025)

Positive contributions of China's protected areas in biodiversity conservation and carbon storage under future climate change - Xuede Dong; Jirui Gong; Frank Yonghong Li; Lingfeng Mao; Weiyuan Zhang; Siqi Zhang; Guisen Yang; Chenyi Yan; Ruijing Wang; Shangpeng Zhang; Tong Wang (Science of The Total Environment, 2025)

Antarctic circumpolar current evolution and its relation to southern hemisphere westerly winds during the holocene - Lingfeng Wan; Dapeng Li; Chenyu Zhu; Zhengyu Liu; Shaoqing Zhang; Xiaopei Lin; Jiuyou Lu (Climate Dynamics, 2025)

Correction: Divergent dominant physical processes of extreme heatwaves in northern and southern China - Yueyang Ni; Bo Qiu; Yipeng Cao; Xin Miao; Lingfeng Li; Jiuyi Chen; Siwen Zhao; Xiaohui Tian; Weidong Guo (Climate Dynamics, 2025)

Late Oligocene paleosols in the Haltang Basin of northeastern Tibetan Plateau and their implications for the early extent of the Asian monsoon - Zhaobin Zhang; Shuang Dai; Xinnan Fang; Xiaojun Ma; Yufan Zhang; Zhongzhao Ding; Lingfeng Qin; Chunyan Li; Meng Zhou; Tianqi Ji; Jie Yang (Palaeogeography, Palaeoclimatology, Palaeoecology, 2025)

High-throughput screening and inhibition mechanism analysis of Bacillus licheniformis BL-4 as an antagonistic strain for Lactobacillus panis - Lingfeng Yi; Xinyue Li; Menglin She; Yaokang Wu; Jianghua Li; Guocheng Du; Long Liu; Li Wang; Yanfeng Liu (Systems Microbiology and Biomanufacturing, 2025)

Prediction of BDS-3 satellite clock bias based on EWT-LSTM ensemble model - Kaihui Lv; Chenglin Cai; Yihao Cai; Wenhui Guan; Zexian Li; Lingfeng Cheng; Yun Fang (GPS Solutions, 2025)

Targeting Nrf2 by bioactive peptides alleviate inflammation: expanding the role of gut microbiota and metabolites - Zhongxing Chu; Lingfeng Zhu; Yaping Zhou; Feiyan Yang; Zuomin Hu; Yi Luo; Wen Li; Feijun Luo (Critical Reviews in Food Science and Nutrition, 2025)

Characteristics of phosphorus distribution and mechanisms of phosphorus release through migration and transformation in the sediments of deep-water reservoirs in mountainous areas - Lingfeng Wang; Feng Zhong; Haibo Li; Zhenbo Sun; Wenjie He (Journal of Environmental Chemical Engineering, 2025)

Temporal and spatial differentiation in the landslide sediment transfer potential in Wenchuan earthquake-impacted areas - Jiang Xiong; Huayong Chen; Chuan Tang; Ming Chen; Jiangang Chen; Tao Yang; Lingfeng Gong; Qingyun Shi; Xianzheng Zhang; Ning Li; Mingwei Li (Landslides, 2025)

Safety and Probiotics Evaluation of Bifidobacterial Genomes Isolated from Probiotic Products - Jue Li; Yinhuan Wang; Xingyu Xu; Xiaoling Zheng; Zhengnan Wang; Xiaofeng Chen; Lei Wang; Lingfeng Mao; Wangqin Ge; Huijun Liu; Wenwen Gao; Tingzhang Wang; et al. (Current Microbiology, 2025)

Shell Colour Diversity in Marine Molluscs: From Current Knowledge to Future Aquaculture Applications - Biyang Hu; Hong Yu; Chengxun Xu; Lingfeng Kong; Shikai Liu; Qi Li (Reviews in Aquaculture, 2025)
Mollusc shell colour represents an important economic trait contributing to product marketability in aquaculture. Marine molluscs with diverse shell colours and patterns are valuable models for animal colouration mechanisms study. Recent progress in marine mollusc shell colour research has been propelled by investigations of shell‐colour variants, advancements in high‐throughput sequencing technologies, and research into metabolic regulatory mechanisms for pigment biosynthesis. This review synthesizes current advancements in genetic architecture, gene regulatory networks and pigment metabolic processes governing shell colour variation in marine molluscs. In this review, insights gained from genetic studies uncover diverse inheritance patterns, key loci and present shell‐colour‐related transcriptomic datasets along with integrative multi‐omics studies. Moreover, distribution, metabolic networks and functional gene linkages of major pigments (melanin, carotenoids, and porphyrins) are characterized, while ommochromes are also discussed. Furthermore, environmental, dietary and structural factors influencing shell colour are listed. By synthesizing current findings, this review offers a detailed overview of the common factors influencing shell colour across marine mollusc species and probes the potential implications of shell colour studies for aquaculture. Future research directions emphasize pigment characterization, pigment transport mechanism studies and integrative multi‐omics approaches to bridge genetic and chemical understandings. In summary, this review outlines the current progress on marine mollusc shell colouration, provides referable research directions on shell‐colour‐related molluscs, and enhances understanding of animal colouration mechanisms.

Bond durability between GFRP bars and seawater sea sand concrete in marine environments - Guanghao Mai; Zhe Xiong; Haoran Zhou; Lingfeng Zhou; Huanyu Zhu; Lijuan Li (Engineering Structures, 2025)

Surface passivated 3D halide perovskite single crystal by 2D perovskite towards high performance soft X-ray detection and gamma-ray spectrum - Yan Xiong; Min Li; Shunsheng Yuan; Yuting Liu; Tong Jin; Jincong Pang; Sihao Xia; Mingquan Liao; Lingling Liu; Lingfeng Wu; Kuan Yew Cheong; Huayang Yu; et al. (Chemical Engineering Journal, 2025)

Risk prediction of catastrophic debris flows against the background of material changes and human engineering activity in the Wenchuan earthquake disturbance area - Jiang Xiong; Huayong Chen; Chuan Tang; Wanyu Zhao; Ming Chen; Tao Yang; Lingfeng Gong; Xianzheng Zhang; Qingyun Shi; Ning Li; Jiangang Chen (Bulletin of Engineering Geology and the Environment, 2025)

Co-infection by RGNNV and V. rotiferianus in golden pompano: Insights into disease risks and immune responses - Xinshuai Li; Lingfeng Guan; Cuiyu Liu; Jinpeng Chen; Xin He; Yanwei Li; Shaowen Wang; Qiwei Qin; Min Yang (Aquaculture, 2025)

A 1D spectral approach for efficient modal identification of thin-walled members in shell finite element models - Yiling Dai; Shaokuai Wang; Mingming Xiang; Lingfeng Yin; Zhanjie Li (Engineering Structures, 2025)

Preparation of SCOF/UiO-66-NH2 immobilized laccase biocatalytic membrane for micropollutants removal from water - Tiantian Wang; Lingfeng Zhao; Guanhua Liu; Xiaoyang Yue; Xiaobing Zheng; Li Ma; Yunting Liu; Mimi Chen; Yanjun Jiang (Chemical Engineering Journal, 2025)

Geomorphometric assessment of spatial transfer potential of landslides sediment in seismically impacted areas - Jiang Xiong; Huayong Chen; Chuan Tang; Chenxiao Tang; Lingfeng Gong; Ming Chen; Xianzheng Zhang; Tao Yang; Ning Li; Qingyun Shi; Mingwei Li (Natural Hazards, 2025)

DOPA Decarboxylase (DDC) in Pacific Oysters: Characterization and Role in Tyrosine Metabolism and Melanogenesis - Kunyin Jiang; Hong Yu; Lingfeng Kong; Shikai Liu; Shaojun Du; Qi Li (Marine Biotechnology, 2025)

Divergent dominant physical processes of extreme heatwaves in northern and southern China - Yueyang Ni; Bo Qiu; Yipeng Cao; Xin Miao; Lingfeng Li; Jiuyi Chen; Siwen Zhao; Xiaohui Tian; Weidong Guo (Climate Dynamics, 2025)

Advanced design of the crushing chamber for the sugarcane top silage cutter in harvester with experiments and simulation - Peng Huo; Shaochun Ma; Jun Qian; Weiqing Li; Baocheng Zhou; Wei Liu; Wenpeng Liang; Wenzhi Li; Changyu Wang; Sha Yang; Lingfeng Li; Yechen Li; et al. (Computers and Electronics in Agriculture, 2025)

Co-infection of nervous necrosis virus and Vibrio harveyi increased mortality and worsened the disease severity in the orange-spotted grouper (Epinephelus coioides) - Lingfeng Guan; Xinshuai Li; Jinpeng Chen; Liqun Wang; Xinyue Zhang; Hongyan Sun; Yanwei Li; Min Yang; Qiwei Qin; Shaowen Wang (Fish & Shellfish Immunology, 2025)

A robust index was extracted to assess the prolonged changes in debris flow activity after a high magnitude earthquake - Jiang Xiong; Huayong Chen; Chuan Tang; Chenxiao Tang; Jiangang Chen; Tao Yang; Lingfeng Gong; Ming Chen; Qingyun Shi; Ning Li (CATENA, 2025)

CgPPOX and CgFECH Mediate Protoporphyrin IX Accumulation Predominantly in the Outer Mantle Fold of Pacific Oyster Crassostrea gigas - Biyang Hu; Hong Yu; Lingfeng Kong; Shikai Liu; Shaojun Du; Qi Li (Marine Biotechnology, 2025)

DNA Methylation of Somatic Tissues in Oysters is Influenced by Sex and Heredity - Wen Teng; Chengxun Xu; Shikai Liu; Hong Yu; Lingfeng Kong; Qi Li (Marine Biotechnology, 2025)

Dynamic impact of hillslope landslide sediment transfer to ecological environment recovery in earthquake disturbed area - Jiang Xiong; Huayong Chen; Chuan Tang; Ming Chen; Tao Yang; Lingfeng Gong; Xianzheng Zhang; Qingyun Shi; Ning Li; Mingwei Li (Bulletin of Engineering Geology and the Environment, 2025)

Examination of the roles of CgTH in tyrosine metabolism and pigmentation of Pacific oyster (Crassostrea gigas) - Kunyin Jiang; Hong Yu; Lingfeng Kong; Shikai Liu; Shaojun Du; Qi Li (Aquaculture, 2025)

Impact performance of curved double arrow and stacked Miura-ori panels - Zhejian Li; Lingfeng Wang; Ruofei Yan; Yuanpeng He; Hong Hao; Yuanzheng Lin; Wensu Chen (Engineering Structures, 2025)

Co-grown novel S-scheme tubular P–UCN/S-TCN homojunction mediates photocatalysis-PMS activation synergistic system for efficient degradation of antibiotic - Ting Wu; Zhifeng Liu; Binbin Shao; Yuan Pan; Qingyun He; Xiansheng Zhang; Lingfeng Zhou; Yunze Wang; Teng Li; Sheng Liu (Chemosphere, 2024)

Double network hydrogel confined MXene/Liquid metal by dynamic hydrogen bond for high-performance wearable sensors - Yuanwan Lou; Jingkun Wang; Yubo Peng; Xiaona Wang; Jianan Zhang; Lingfeng Chen; Wenchao Gao; Zhipeng Gao; Xiaona Li; Weiyi Chen; Min Zhao (Chemical Engineering Journal, 2024)

Increased microgastropoda sampling give new insights into the phylogenetic relationships of Littorinoidea (Littorinimorpha) - Lu Qi; Ning Zhang; Biyang Xu; Qinzeng Xu; Xiao Han; Lingfeng Kong; Qi Li (Molecular Phylogenetics and Evolution, 2024)

Characterization of piRNAs in Diploid and Triploid Pacific Oyster Gonads: Exploring Their Potential Roles in Triploid Sterility - Yaru Zhou; Hong Yu; Qi Li; Lingfeng Kong; Shikai Liu; Chengxun Xu (Marine Biotechnology, 2024)

Comparative analysis on growth performance, survival and harvest traits between offspring from wild and mass-selected populations of Crassostrea nippona - Yiming Hu; Qi Li; Chengxun Xu; Shikai Liu; Lingfeng Kong; Hong Yu (Aquaculture, 2024)

OysterDB: A Genome Database for Ostreidae - Xinchun Li; Yitian Bai; Chengxun Xu; Shikai Liu; Hong Yu; Lingfeng Kong; Shaojun Du; Qi Li (Marine Biotechnology, 2024)

Dynamic susceptibility assessment of debris flow hazard after a strong earthquake, Wenchuan County, Sichuan, China - Xianzheng Zhang; Chenxiao Tang; Yongbo Tie; Xiaojuan Li; Chuan Tang; Jiang Xiong; Ming Chen; Lingfeng Gong (Landslides, 2024)

Effect of propranolol on pharmacokinetics of clozapine in schizophrenic patients: a meta-analysis - Xiding Yang; Qiangyong Yan; Lingfeng Yang; Jingjing Li; Xiao Fan; Jindong Chen; Haishan Wu; Yongyu Yang; Ronghua Zhu; Pingfei Fang (European Journal of Clinical Pharmacology, 2024)

Dietary Supplementation of β-Carotene Reveals miRNAs Involved in the Regulation of Carotenoid Metabolism in Crassostrea gigas - Dongfang Sun; Sai Wan; Hong Yu; Lingfeng Kong; Qi Li (Journal of Ocean University of China, 2024)

Impact of dielectric barrier discharge cold plasma on anthocyanin metabolism in blueberries: A targeted metabonomic and transcriptomic analysis - Lingfeng Xu; Zhenbo Gao; Ling Li; Jian Guo (Postharvest Biology and Technology, 2024)

Preparation of bacterial fertilizer from biogas residue after anaerobic co-digestion of kitchen waste and residual sludge - Chuan Li; Chang Hua; Lingling Chen; Zimei Miao; Rui Xu; Sili Peng; Zhiwei Ge; Lingfeng Mao (Environmental Science and Pollution Research, 2024)

Examination of the effects of impaired spermatogenesis on sterility in triploid oysters (Crassostrea gigas), and implications for commercial aquaculture - Chen Chen; Hong Yu; Qi Li; Lingfeng Kong; Shikai Liu; Chengxun Xu (Aquaculture, 2024)

Modulating the acidity and reducibility of FeMn/TiO2 to boost the low-temperature selective catalytic reduction of NOx - Jingyi Zhu; Yuankai Shao; Zhenguo Li; Kaixiang Li; Xiaoning Ren; Lingfeng Jia; Huiquan Li; Huifang Cheng; Jian Liu; Jixing Liu (Fuel, 2024)

Strength and behavior of axially and eccentrically loaded built-up closed sections using four cold-formed steel open sections - Lingfeng Yin; Shaokuai Wang; Yongbiao Wang; Tianyang Deng; Zhanjie Li (Engineering Structures, 2024)

A new multiscale Cosserat model for size effect simulation in granular media - Lingfeng Guo; Xiaolong Li; Lu Ren; Yuanming Lai; Junsheng Chen; Lunyang Zhao (Computers and Geotechnics, 2024)

cAMP-Mediated CREM-MITF-TYR Axis Regulates Melanin Synthesis in Pacific Oysters - Kunyin Jiang; Hong Yu; Lingfeng Kong; Shikai Liu; Qi Li (Marine Biotechnology, 2024)

Experimental and modeling study of ignition delay times of n-C5H12 and C3H6 under O2/CO2 atmospheres - Chao Peng; Chun Zou; Jiaxin Ren; Qianjin Lin; Wenxiang Xia; Lingfeng Dai; Jiacheng Liu; Wenyu Li (Fuel, 2024)

Seipin Deficiency Leads to Energy Dyshomeostasis via Inducing Hypothalamic Neuroinflammation and Aberrant Expression of Neuropeptides - Wenli Cui; Hong Chen; Lingfeng Lei; Wenru Wang; Kah-Leong Lim; Chengwu Zhang; Li Lu (NeuroMolecular Medicine, 2024)

Parallel path following control of cyber-physical maritime autonomous surface ships based on deep neural predictor - Lingfeng Li; Anqing Wang; Bing Han; Dan Wang; Tieshan Li; Zhouhua Peng (Ocean Engineering, 2024)

Differences in the activities of six soil enzymes in response to cadmium contamination of paddy soils in high geological background areas - Juan Liu; Xinyang Li; Qilin Zhu; Jiawen Zhou; Lingfeng Shi; Weihong Lu; Li Bao; Lei Meng; Longhua Wu; Naiming Zhang; Peter Christie (Environmental Pollution, 2024)

Transcriptomic and Physiological Analysis Reveal Melanin Synthesis-Related Genes and Pathways in Pacific Oysters (Crassostrea gigas) - Kunyin Jiang; Chengxun Xu; Hong Yu; Lingfeng Kong; Shikai Liu; Qi Li (Marine Biotechnology, 2024)

Impact of Cross-Limb Stent-Graft Configuration on Hemodynamics in Abdominal Aortic Aneurysm Interventional Therapy - Yanqing Xie; Yating Zhu; Yike Shi; Yawei Zhao; Hongpeng Zhang; Fen Li; Hui Song; Lingfeng Chen; Wei Guo (Cardiovascular Engineering and Technology, 2024)

Potential mobilization of water-dispersible colloidal thallium and arsenic in contaminated soils and sediments in mining areas of southwest China - Yanpei Du; Lingfeng Shi; Xinyang Li; Juan Liu; Rongrong Ying; Pengjie Hu; Longhua Wu; Peter Christie (Journal of Hazardous Materials, 2024)

Genetic improvement of oysters: Current status, challenges, and prospects - Kunyin Jiang; Chen Chen; Gaowei Jiang; Yong Chi; Chengxun Xu; Lingfeng Kong; Hong Yu; Shikai Liu; Qi Li (Reviews in Aquaculture, 2024)
Oysters are one of the most commercially important shellfish species and have been cultured for thousands of years. Oyster aquaculture supports the major aquaculture industries in many countries. Over the last few decades, the oyster breeding and aquaculture industries have developed rapidly to meet the continually growing demand. Many researchers have made significant efforts toward the genetic improvement of commercially important traits in oysters. Some strains with fast‐growing, disease‐resistant, and stable shell‐colours have been developed through selective breeding. Some hybrid varieties have been developed by crossing different geographical populations or cultivated strains. Several hybrids exhibit considerable genetic variation and improved productive performance. Additionally, polyploid induction technologies have been applied in the oyster aquaculture industry, which provides a useful tool for performance improvement and genetic containment of cultured stocks. At present, the development of molecular breeding also provides a great opportunity for oyster genetic improvement. These advances in oyster breeding have improved the quality of oysters, brought great economic benefits, and been conducive to the sustainability of oyster production. Nonetheless, there are still some limitations and obstacles in oyster breeding, such as infectious diseases, summer mortality, conservation of germplasm resources, environmental contamination, and climate change. The present review provides an overview of the current status, challenges, and prospects in oyster breeding.

Effects of cadmium exposure during pregnancy on genome-wide DNA methylation and the CREB/CREM pathway in the testes of male offspring rats - Xiushuai Du; Jianlin Zhu; Xueming Xu; Zhilan Lu; Xiaoqin Li; Yuchen Li; Lingfeng Luo; Wenchang Zhang; Jin Liu (Chemosphere, 2024)

Exposure, bioaccumulation, and risk assessment of organophosphate flame retardants in crayfish in the middle and lower reaches of the Yangtze River - Qiuhong Peng; Lingfeng Peng; Jin Liu; Yan Liu; Xin Liu; Jiaojiao Yin; Shuo Duan; Xiaofang Liu; Yuzhi Li; Zhiyong Gong; Qiao Wang (Science of The Total Environment, 2024)

Numerical investigation on the spray characteristics of biodiesel with gas-assisted atomization injection - Rui Liu; Lingfeng Zhong; Songhong Li; Jing Li; Haocheng Ji (Fuel, 2024)

Photothermal microneedle patch loaded with antimicrobial peptide/MnO2 hybrid nanoparticles for chronic wound healing - Guanyi Wang; Wang Wang; Zesheng Chen; Tao Hu; Lingfeng Tu; Xiaolong Wang; Weikang Hu; Sheng Li; Zijian Wang (Chemical Engineering Journal, 2024)

MOF derived MnFeOX supported on carbon cloth as electrochemical anode for peroxymonosulfate electro-activation and persistent organic pollutants degradation - Xiansheng Zhang; Yuan Pan; Yunze Wang; Ting Wu; Binbin Shao; Qingyun He; Lingfeng Zhou; Teng Li; Sheng Liu; Xinyi Huang; Zhifeng Liu (Chemical Engineering Journal, 2024)

Application of 3D hierarchical porous NiCo-spinel nanosheet array for enhancement of synergistic activation of peroxymonosulfate: Degradation, Intermediates, mechanism and degradation pathway of tetracycline - Yuan Pan; Xiansheng Zhang; Ting Wu; Binbin Shao; Teng Li; Qingyun He; Zehua Chen; Lingfeng Zhou; Sheng Liu; Xinyi Huang; Zhifeng Liu (Chemical Engineering Journal, 2024)

An integrated analysis of the fecal metabolome and metagenome reveals the distinct effects of differentially charged nanoplastics on the gut microbiota-associated metabolites in mice - Miaomiao Teng; Xiaoli Zhao; Lingfeng Zhou; Hong Yan; Lihui Zhao; Jiaqi Sun; Yunxia Li; Wentao Zhu; Fengchang Wu (Science of The Total Environment, 2024)

Saving the overlooked mangrove horseshoe crabs-A perspective from enhancing mangrove ecosystem conservation - Yuntian Shi; Shuhui Li; Yaowu Li; Lingfeng Jiang; Fahim Ullah Khan; Khor Waiho; Youji Wang; Menghong Hu (Marine Environmental Research, 2024)

Overlooked fluorine deficiency in children of South and East China may be exacerbated by climate change: Evidence from the national assessment - Lingfeng Zhou; Weigang Liang; Yaobin Meng; Xiaoli Zhao; Fei Guo; Lingling Liu; Wenjing Li; Miaomiao Teng; Fanhao Song; Zhiqiang Cao; Yidong Mi; Qigen Lin; et al. (Journal of Cleaner Production, 2024)

More than just pandas: Urgent research needed on China's native plant biodiversity - Yu-heng Chen; Yao Li; Yu-ran Dong; Min Zhang; Yong Yang; Richard B. Primack; Kathryn E. Barry; Lingfeng Mao (Biological Conservation, 2024)

A low-carbon CO2 ice rink technology for the Winter Olympics - Ligeng Li; Kai Liu; Hua Tian; Jinwen Cai; Christos N Markides; Jingyu Wang; Lingfeng Shi; Xuan Wang; Yitai Ma; Xingyu Liang; Gequn Shu (Science Bulletin, 2023)

3D binder-free nanoarchitecture design of porous silicon/graphene fibers for ultrastable lithium storage - Yongbiao Mu; Ruijie Zhang; Bu-ke Wu; Ming Yang; Youqi Chu; Qing Zhang; Lingfeng Zou; Xianbin Wei; Zifan Liao; Haixiang Ren; Yiju Li; Lin Zeng (Chemical Engineering Journal, 2023)

Contraction of Heat Shock Protein 70 Genes Uncovers Heat Adaptability of Ostrea denselamellosa - Zhen Dong; Shikai Liu; Hong Yu; Lingfeng Kong; Qi Li (Journal of Ocean University of China, 2023)

An improved frequency-domain model for the supercritical flow instability analysis in vertical tubes - Lingfeng Bi; Xirong Zhang; Weiteng Li; Tingyu Chen; Xiaocheng Du; Dong Yang (Annals of Nuclear Energy, 2023)

Application of remote sensing monitoring to the spatiotemporal variation in debris flow activity in the catastrophic Wenchuan seismic area - Jiang Xiong; Huayong Chen; Chuan Tang; Ming Chen; Ming Chang; Xianzheng Zhang; Lingfeng Gong; Ning Li; Qingyun Shi; Mingwei Li (CATENA, 2023)

Experimental studies on active oxygen control performance of solid PbO mass exchanger in liquid lead–bismuth eutectic loop - Ruixian Liang; Huiping Zhu; Zhenhua Sheng; Xiaobo Li; Muran Qi; Yifeng Wang; Lingfeng Yang; Xu Tu; Hao Wu; Fang Liu; Zhangpeng Guo; Haicai Lyu; et al. (Annals of Nuclear Energy, 2023)

Parallel evolution in Crassostrea oysters along the latitudinal gradient is associated with variation in multiple genes involved in adipogenesis - Wen Teng; Huiru Fu; Zhuanzhuan Li; Qian Zhang; Chengxun Xu; Hong Yu; Lingfeng Kong; Shikai Liu; Qi Li (Molecular Ecology, 2023)
Parallel diversification provides a proper framework for studying the role of natural selection in evolution. Yet, empirical studies from ecological ‘non‐model’ species of invertebrates are limited at the whole genome level. Here, we presented a chromosome‐scale genome assembly for Crassostrea angulata and investigated the parallel genomic evolution in oysters. Specifically, we used population genomics approaches to compare two southern–northern oyster species pairs ( C . angulata – C . gigas and southern–northern C . ariakensis ) along the coast of China. The estimated divergence time of C . angulata and C . gigas is earlier than that of southern and northern C . ariakensis , which aligns with the overall elevated genome‐wide divergence. However, the southern–northern C . ariakensis F ST profile represented more extremely divergent “islands”. Combined with recent reciprocal hybridization studies, we proposed that they are currently at an early stage of speciation. These two southern–northern oyster species pairs exhibited significant repeatability in patterns of genome‐wide differentiation, especially in genomic regions with extremely high and low divergence. This suggested that divergent and purifying selection has contributed to the genomic parallelism between southern and northern latitudes. Top differentiated genomic regions shared in these two oyster species pairs contained candidate genes enriched for functions in energy metabolism, especially adipogenesis, which are closely related to reproductive behaviours. These genes might be good candidates for further investigation in vivo. In conclusion, our results suggest that similar divergent selection and shared genomic features could predictably transform standing genetic variation within one species pair into differences in another.

Performance of potentiometric oxygen sensors with LSCF electrode in lead–bismuth eutectic loop - Ruixian Liang; Huiping Zhu; Lingfeng Yang; Muran Qi; Xiaobo Li; Yifeng Wang; Zhenhua Sheng; Xu Tu; Gaoxiang Xu; Boqing Li; Hao Wu; Haicai Lyu; et al. (Annals of Nuclear Energy, 2023)

Molecular-level insights into the heterogeneous variations and dynamic formation mechanism of leached dissolved organic matter during the photoaging of polystyrene microplastics - Fanhao Song; Tingting Li; Jin Hur; Quan Shi; Fengchang Wu; Wei He; Di Shi; Chen He; Lingfeng Zhou; Mingqi Ruan; Yuhan Cao (Water Research, 2023)

Solvent effect to modulate nitrogen dopant in Co-N-C catalysts for oxygen reduction reaction acceleration - Lingfeng Li; Guokang Han; Yandi Wen; Yuxin Liu; Rang Xiao; Wei Zhang; Fanpeng Kong; Lei Du; Yulin Ma; Pengjian Zuo; Chunyu Du; Geping Yin (Fuel, 2023)

Low-photovoltage-loss pringting perovskite solar cells in ambient air through ink synergistic engineering - Yifan Lv; Kaiyu Wang; Ai Lan; Lingfeng Chao; Changshun Chen; Jinpei Wang; Qing Yao; Jianxin Chen; Tengfei Pan; Yajing Li; Hui Zhang; Yingdong Xia; et al. (Chemical Engineering Journal, 2023)

Effects of Dietary Cystine and Tyrosine Supplementation on Melanin Synthesis in the Pacific Oyster (Crassostrea gigas) - Zhuanzhuan Li; Chengxun Xu; Hong Yu; Lingfeng Kong; Shikai Liu; Qi Li (Marine Biotechnology, 2023)

Mitogenomic phylogeny of Muricidae (Gastropoda: Neogastropoda) - Yi Yu; Lingfeng Kong; Qi Li (Zoologica Scripta, 2023)
Muricidae is one of the most species‐rich and morphologically diverse families in Gastropoda, with a worldwide distribution. The classification of Muricidae has traditionally been based on shell and radular characteristics; however, the phylogenetic relationships within the family are debated due to morphological convergence and plasticity. In this study, to explore the phylogenetic relationships of Muricidae, we sequenced 11 muricid mitochondrial (mt) genomes and compared them with 13 previously reported complete muricid mt genomes. All muricid mt genomes shared the same gene arrangement and exhibited conserved genome size and nucleotide composition. Three‐nucleotide deletions in atp8 and nad4 , and three‐nucleotide insertions in nad2 were detected in Rapaninae. Both maximum likelihood and Bayesian inference analyses supported the monophyly of each subfamily studied (Ocenebrinae, Muricinae, Rapaninae and Ergalataxinae). Ergalataxinae was recovered as the sister taxon of Rapaninae, refuting the traditional morphology‐based placement of Ergalataxinae within Rapaninae. In Rapaninae, Indothais was confirmed to be monophyletic and determined to be a valid genus. Similarly, Drupina was determined to be an independent genus rather than a subgenus of Drupa . Purpura was recovered as a paraphyletic group, with Purpura panama being sister to Reishia + Rapana + Indothais and clustering with Purpura bufo .

Phylogenomic resolution of Imparidentia (Mollusca: Bivalvia) diversification through mitochondrial genomes - Yu Wang; Yi Yang; Lingfeng Kong; Takenori Sasaki; Qi Li (Marine Life Science & Technology, 2023)
Despite significant advances in the phylogenomics of bivalves over the past decade, the higher-level phylogeny of Imparidentia (a superorder of Heterodonta) remains elusive. Here, a total of five new mitochondrial sequences ( Chama asperella , Chama limbula , Chama dunkeri , Barnea manilensis and Ctena divergens ) was added to provide resolution in nodes that required additional study . Although the monophyly of Lucinida remains less clear, the results revealed the overall backbone of the Imparidentia tree and the monophyly of Imparidentia. Likewise, most relationships among the five major Imparidentia lineages—Lucinida, Cardiida, Adapedonta, Myida and Venerida—were addressed with a well-supported topology. Basal relationships of Imparidentia recovered Lucinidae as the sister group to all remaining imparidentian taxa. Thyasiridae is a sister group to other imparidentian bivalves (except Lucinidae species) which is split into Cardiida, Adapedonta and the divergent clade of Neoheterodontei. Neoheterodontei was comprised of Venerida and Myida, the former of which now also contains Chamidae as the sister group to all the remaining venerid taxa. Moreover, molecular divergence times were inferred by calibrating nine nodes in the Imparidentia tree of life by extinct taxa. The origin of these major clades ranged from Ordovician to Permian with the diversification through the Palaeozoic to Mesozoic. Overall, the results obtained in this study demonstrate a better-resolved Imparidentia phylogeny based on mitochondrial genomes.

Effect of extreme pH conditions on methanogenesis: Methanogen metabolism and community structure - Shuang Qiu; Xingchen Zhang; Wenhao Xia; Zimu Li; Lingfeng Wang; Zhipeng Chen; Shijian Ge (Science of The Total Environment, 2023)

Investigating the spatial–temporal changes of flood events across the Yangtze River Basin, China: Identification, spatial heterogeneity, and dominant impact factors - Jiarui Yu; Lei Zou; Jun Xia; Yongyong Zhang; Lingfeng Zuo; Xiaoyang Li (Journal of Hydrology, 2023)

Synergistic structure of LiFeO2 and Fe2O3 layers with electrostatic shielding effect to suppress surface lattice oxygen release of Ni-rich cathode - Youqi Chu; Yongbiao Mu; Lingfeng Zou; Jie Cheng; Shibo Xi; Qichang Pan; Meisheng Han; Hongqiang Wang; Qingyu Li; Fenghua Zheng; Qing Zhang; Lin Zeng (Chemical Engineering Journal, 2023)

Fabrication of immobilized lipases for efficient preparation of 1,3-dioleoyl-2-palmitoylglycerol - Lihong He; Can Zeng; Lingfeng Wei; Li Xu; Fenglin Song; Jianrong Huang; Nanjing Zhong (Food Chemistry, 2023)

Spatio-temporal heterogeneity in the international trade resilience during COVID-19 - Wei Luo; Lingfeng He; Zihui Yang; Shirui Zhang; Yong Wang; Dianbo Liu; Sheng Hu; Li He; Jizhe Xia; Min Chen (Applied Geography, 2023)

Sugarcane leaf-stalk separating technology: A critical review - Peng Huo; Shaochun Ma; Chenyang Su; Zhengliang Ding; Weiqing Li; Jun Qian; Lingfeng Li; Yechen Li; Baocheng Zhou; Chong Peng; Wenzhi Li (Biosystems Engineering, 2023)

Halide-chalcogenide hetero-structure for efficient and stable perovskite solar cells - Riming Nie; Zeliang Wei; Aarti Mehta; Lingfeng Chao; Jiaxing Gao; Weicun Chu; Zhongping Li; Han Miao; Yonghua Chen; Wanlin Guo (Chemical Engineering Journal, 2023)

Ultrasonic Sensor-Based Basecutter Height Control System of Sugarcane Harvester - Zhengliang Ding; Shaochun Ma; Xiadong Zhang; Wenpeng Liang; Lingfeng Li; Chenyang Su (Sugar Tech, 2023)

Transcriptome Analysis of Reciprocal Hybrids Between Crassostrea gigas and C. angulata Reveals the Potential Mechanisms Underlying Thermo-Resistant Heterosis - Gaowei Jiang; Yin Li; Geng Cheng; Kunyin Jiang; Jianmin Zhou; Chengxun Xu; Lingfeng Kong; Hong Yu; Shikai Liu; Qi Li (Marine Biotechnology, 2023)

A self-powered wearable piezoelectric nanogenerator for physiological monitoring based on lead zirconate titanate/microfibrillated cellulose@polyvinyl alcohol (PZT/MFC@PVA) composition - Yanfang Guan; Mingyang Bai; Qilong Wang; Lei Liu; Shaobo Yu; Bingru Kong; Feng Lv; Mingshuo Guo; Guangyu Liu; Lingfeng Li; Lin Zhang; Yang Lin; et al. (Chemical Engineering Journal, 2023)

A multicentre study on the incidence of respiratory viruses in children with community-acquired pneumonia requiring hospitalization in the setting of the zero-COVID policy in China - Ziheng Feng; Baoping Xu; Lili Zhong; Jing Chen; Jikui Deng; Zhengxiu Luo; Lingfeng Cao; Yu Tang; Changchong Li; Rong Jin; Li Deng; Yunxiao Shang; et al. (Archives of Virology, 2023)
Background Stringent nonpharmaceutical interventions (NPIs) have been implemented worldwide to combat the COVID-19 pandemic, and the circulation and seasonality of common respiratory viruses have subsequently changed. There have been few multicentre studies or comparisons of the prevalence of respiratory viruses accounting for community-acquired pneumonia (CAP) in hospitalized children between the pre-COVID period and the period after community and school reopening in the setting of the zero-COVID policy. Methods We included 1543 children with CAP who required hospitalization from November 1, 2020 to April 30, 2021 (period 1), and 629 children with the same conditions from November 1, 2018, to April 30, 2019 (period 2), in our study. All respiratory samples from these patients were screened for six respiratory viruses (respiratory syncytial virus [RSV], adenovirus [ADV], influenza A virus [Flu A], influenza B virus [Flu B], parainfluenza virus type 1 [PIV1], and parainfluenza virus type 3 [PIV3]) using a multiplex real-time PCR assay. Results and conclusions The median ages of the enrolled patients at the time of diagnosis were 1.5 years and 1.0 years for period 1 and period 2, respectively. In period 1, viral pathogens were detected in 50.3% (776/1543) of the enrolled patients. The most frequently identified viral pathogen was RSV (35.9%, 554/1543), followed by PIV3 (9.6%, 148/1543), PIV1 (3.6%, 56/1543), ADV (3.4%, 52/1543), Flu A (1.0%, 16/1543), and Flu B (0.8%, 13/1543). The total detection rates of these six viruses in the peak season of CAP were at the pre-COVID level. The prevalence of Flu A decreased dramatically, and circulation activity was low compared to pre-COVID levels, while the incidence of PIV3 increased significantly. There were no significant differences in the detection rates of RSV, ADV, Flu B, and PIV1 between the two periods. Our results showed that respiratory viruses accounted for CAP in hospitalized children at pre-COVID levels as communities and schools reopened within the zero-COVID policy, although the prevalence aetiology spectrum varied.

A Comparative Study on the Difference in Temperature and Salinity Tolerance of Crassostrea nippona and C. gigas Spat - Yiming Hu; Qi Li; Chengxun Xu; Shikai Liu; Lingfeng Kong; Hong Yu (Journal of Marine Science and Engineering, 2023)
Although Crassostrea nippona and C. gigas are occasionally found to be sympatric, little is known about the differences in tolerance against environmental stresses between species, which may potentially result in severe economic losses due to the neglect of species-specific biological characteristics in farming practices. Therefore, two independent and consecutive experiments were performed to evaluate the differences in temperature and salinity tolerance between C. nippona and C. gigas spat and determine the optimal environmental conditions for the aquaculture of C. nippona spat. The experimental results of dynamic treatment showed that the accumulative survival rate (ASR) of C. nippona spat was generally lower than that of C. gigas throughout temperature changes and salinity decreases, while the ASR of C. nippona spat was superior to that of C. gigas with increasing salinity. In addition, the daily growth rate (DGR) of both species was significantly inhibited at 18 °C and peaked at 25 °C with increasing temperature (p

Fast satellite selection algorithm for GNSS multi-system based on Sherman–Morrison formula - Junpeng Shi; Kezhao Li; Lin Chai; Lingfeng Liang; Chendong Tian; Keke Xu (GPS Solutions, 2023)
Efficient use of global navigation satellite system (GNSS) observations improves when applying rational satellite selection algorithms. By combining the Sherman–Morrison formula and singular value decomposition, a smaller-GDOP (geometric dilution of precision)-value method is proven for an increasing number of visible satellites. By combining this smaller-GDOP-value method with the maximum-volume-tetrahedron method, a new rapid satellite selection algorithm based on the Sherman–Morrison formula for GNSS multi-systems is proposed. The basic idea of the algorithm is as follows: First, the maximum-volume-tetrahedron method is used to obtain four initial visible satellites. Then, the other visible satellites are selected by using the smaller-GDOP-value method to reduce the GDOP value and improve the accuracy of the overall algorithm. When the number of included satellites reaches a certain value, the rate of GDOP decrease tends to approach zero. Considering the algorithm precision and the computation efficiency, reasonable thresholds and end of calculation condition equation are given, which can make the proposed algorithm autonomous. The reasonable thresholds and the end of calculation parameters are suggested by means of experiments. Under the thresholds and the end of calculation parameters, the algorithm has an adaptive functionality. Furthermore, the GDOP values of the algorithm are less than 2, indicating that this algorithm can meet one of the requirements of high-precision navigation. Moreover, compared with the computation complexity values of the optimal GDOP estimation method, which includes all visible satellites, the values of the new algorithm are about half, indicating that this algorithm has a rapid performance. These findings verify that the proposed satellite selection algorithm based on the Sherman–Morrison formula provides autonomous functionality, high-performance computing, and high-accuracy results.

Improved phylogenetic resolution within Neritidae (Gastropoda, Nertimorpha) with implications for the evolution of shell traits and habitat - Lu Qi; Biyang Xu; Lingfeng Kong; Qi Li (Zoologica Scripta, 2023)
Neritidae is a species‐rich family with substantial interspecific morphological and ecological diversities. The current classification of Neritidae is controversial, particularly regarding the taxonomic position of Smaragdiinae. Although several molecular phylogenetic studies have attempted to clarify the phylogeny of Neritidae, the internal evolutionary relationships have not been completely resolved due to limited sampling. We recently sequenced eight mitochondrial genomes of Neritidae, reassembled five previously published transcriptome data, and reconstructed a comprehensive phylogeny for Neritidae with mitochondrial genome (13 protein‐coding genes) datasets of up to 23 species. Phylogenetic analyses using maximum likelihood and Bayesian inference indicated that the Neritidae were divided into two monophyletic groups, Neritinae and Neritininae, with strong support. A representative of Smaragdiinae, Smaragdia rangiana , was found to nest within Neritininae. Within Neritininae, the monophyly of Clithon and Neritina has not been recovered. Ancestral state reconstruction indicated that the most recent common ancestor of the Neritidae was a smooth shell. Our results imply at least two transitions from marine to brackish habitats within Neritidae.

Interaction among soil nutrients, plant diversity and hypogeal fungal trophic guild modifies root-associated fungal diversity in coniferous forests of Chinese Southern Himalayas - Nan Yang; Yan Zhang; Jingji Li; Xiuxiu Li; Honghua Ruan; Parag Bhople; Katharina Keiblinger; Lingfeng Mao; Dong Liu (Plant and Soil, 2022)

The effects of natural weathering ages on mineralogical, physical, and chemical properties of stacking molybdenum tailings - Li Wang; Lingfeng Shen; Wei Sun; Bin Ji; Honghu Tang (Environmental Science and Pollution Research, 2022)

Identification of ferroptosis-related signature with potential implications in prognosis and immunotherapy of renal cell carcinoma - Lingfeng Liu; Huan Jin; Mengyuan Dong; Jingwen Tian; Hongsheng Li; Quentin Liu; Yibing Chen; Zhengzhi Zou (Apoptosis, 2022)

Synthesis of Lanthanum-Modified Attapulgite and Its Phosphorus-Fixing Mechanism for Urban Eutrophic Lake - Lingfeng Ye; Ye Li; Cong Liu; Bolin Li; Dongxue Liu; Chang Liu; Jie Wan; Chengbin Fu (Water, Air, & Soil Pollution, 2022)

Effect of Angiogenesis in Bone Tissue Engineering - Jianhao Huang; Qixiu Han; Meng Cai; Jie Zhu; Lan Li; Lingfeng Yu; Zhen Wang; Gentao Fan; Yan Zhu; Jingwei Lu; Guangxin Zhou (Annals of Biomedical Engineering, 2022)

Estimating the Impact of a Seasonal Fishing Moratorium on the East China Sea Ecosystem From 1997 to 2018 - Lingyan Xu; Puqing Song; Yuyu Wang; Bin Xie; Lingfeng Huang; Yuan Li; Xinqing Zheng; Longshan Lin (Frontiers in Marine Science, 2022)
Fisheries management policies (FMPs) have been implemented in coastal countries to ensure a sustainable supply of seafood and the recovery of species diversity. Because of the depletion of fishery stocks, China has introduced a series of FMPs since 1995, including a seasonal fishing moratorium (SFM), a zero-growth strategy, and a minimum mesh size for fishing nets. Here, we built two mass balance models for 1997–2000 (M1997) and 2018–2019 (M2018) using Ecopath with Ecosim 6.6 to illustrate the interannual changes over the past two decades in the East China Sea (ECS). We then simulated two dynamic scenarios from 1997 to 2018, SFM (M2018 SFM ) and no SFM (M2018 no-SFM ), to test the role of the SFM under fishing pressure in the ECS. Ecopath showed that the ECS ecosystem is becoming more mature, although it is still unstable, featuring lower total primary production/total respiration, longer cycles, faster organic material circulation speed, and a higher omnivorous degree. This suggests a slow recovery for the ECS ecosystem in the past two decades. The biomass of fish in the ECS—especially the planktivores, dominated by small-sized Benthosema pterotum —significantly increased in M2018 versus M1997, but there were fewer medium- and large-sized fish. The keystone species switched from the planktivores/piscivores dominated by Decapterus maruadsi in M1997 to planktivores in M2018. Ecosim illustrated that the SFM has positive effects on fishery resources recovery, especially for commercial fishes (i.e., large yellow croakers and hairtails), as reflected by the significantly higher predicted biomass of fish in M2018 SFM compared to M2018 no-SFM and M1997, although the bioaccumulation was consumed by the intense fishing pressure after the SFM. However, the M2018 SFM prediction for nektons was still lower than the actual value, especially for planktivores, which display a sharp increase in biomass. This should be partly attributable to the policy of the minimum mesh size (<5 cm was banned), which benefits B. pterotum due to its 3.5 cm maximum body size. Therefore, a series of FMPs, rather than only the SFM, functioned together in the ECS ecosystem. However, the mixed trophic impact indicated a negative impact if the fisheries were further developed. Fishery management in the ECS needs to be strengthened by extending the SFM and reducing fishing pressure after the SFM.

The Clam Cyclina sinensis (Gmelin) Phylogeography Study with 28S rRNA Gene and Potential of Nuclear rRNA Genes in Genetic Assessments of Molluscs - Gang Ni; Qi Li; Lingfeng Kong; Hong Yu (Journal of Ocean University of China, 2022)

Mitogenomics reveals phylogenetic relationships of Patellogastropoda (Mollusca, Gastropoda) and dynamic gene rearrangements - Tao Xu; Lu Qi; Lingfeng Kong; Qi Li (Zoologica Scripta, 2022)
Patellogastropoda has been recognized as the most ‘primitive’ group of living Gastropoda and plays important role in littoral marine ecosystems. Both morphological and molecular works have attempted to resolve the phylogenetic framework of Patellogastropoda, but evolutionary relationships among major lineages remain controversial. In addition, a few mitogenomes sequenced of Patellogastropoda exhibit extensive rearrangements; however, it was unclear that which one can represent the ancestral gene arrangement. In this regard, we sequenced 10 new mitochondrial genomes and analysed them with previously published nine mitogenomes and six transcriptomic data which represent six families of Patellogastropoda. A well‐supported phylogeny was reconstructed based on the amino acid sequences of 13 protein‐coding genes, recovered Lottioidea as non‐monophyletic with two well‐supported lineages. Comprehensive taxon sampling in Lottiidae allows us to recover Lottia digitalis sister to Lottia cassis . Comparing gene order among families, genera and species showed that Nacellidae has a conserved gene arrangement which is similar to that of hypothetical ancestral Gastropoda, whereas Lottiidae exhibits extensive rearrangements even without considering the changes of tRNA genes. A chronogram dating mayor cladogenetic events within the group was also reconstructed. Our results provide new insights into the phylogenetic relationships of Patellogastropoda and detect dramatic gene rearrangements within the group.

Shell Biosynthesis and Pigmentation as Revealed by the Expression of Tyrosinase and Tyrosinase-like Protein Genes in Pacific Oyster (Crassostrea gigas) with Different Shell Colors - Yijing Zhu; Qi Li; Hong Yu; Shikai Liu; Lingfeng Kong (Marine Biotechnology, 2021)

Relaxation of Selective Constraint on the Ultra-Large Mitochondrial Genomes of Arcidae (Mollusca: Bivalvia) - Shao’e Sun; Qi Li; Lingfeng Kong (Journal of Ocean University of China, 2021)

Faster recovery of soil biodiversity in native species mixture than in Eucalyptus monoculture after 60 years afforestation in tropical degraded coastal terraces - Wenjia Wu; Luhui Kuang; Yue Li; Lingfeng He; Zhijian Mou; Faming Wang; Jing Zhang; Jun Wang; Zhi’an Li; Hans Lambers; Jordi Sardans; Josep Peñuelas; et al. (Global Change Biology, 2021)
Afforestation is an effective method to restore degraded land. Afforestation methods vary in their effects on ecosystem multifunctionality, but their effects on soil biodiversity have been largely overlooked. Here, we mapped the biodiversity and functioning of multiple soil organism groups resulting from diverse afforestation methods in tropical coastal terraces. Sixty years after afforestation from bare land (BL), plant species richness and the abundance of plant litter (398 ± 85 g m −2 ) and plant biomass (179 ± 3.7 t ha −1 ) in native tree species mixtures (MF) were restored to the level of native forests (NF; 287 ± 21 g m −2 and 243.0 ± 33 t ha −1 , respectively), while Eucalyptus monoculture (EP) only successfully restored the litter mass (388 ± 43 g m −2 ) to the level of NF. Soil fertility in EP and MF was increased but remained lower than in NF. For example, soil nitrogen and phosphorus concentrations in MF (1.2 ± 0.2 g kg −1 and 408 ± 49 mg kg −1 , respectively; p −1 and 523 ± 24 mg kg −1 , respectively; p

Molecular Identification of Dried Shellfish Products Sold on the Market Using DNA Barcoding - Shao’e Sun; Xiaojie Zhang; Lingfeng Kong; Qi Li (Journal of Ocean University of China, 2021)

Integrated Analysis of Coding Genes and Non-coding RNAs Associated with Shell Color in the Pacific Oyster (Crassostrea gigas) - Zhuanzhuan Li; Qi Li; Shikai Liu; Ziqiang Han; Lingfeng Kong; Hong Yu (Marine Biotechnology, 2021)

Phylogeny of Veneridae (Bivalvia) based on mitochondrial genomes - Yu Wang; Yi Yang; Hongyue Liu; Lingfeng Kong; Hong Yu; Shikai Liu; Qi Li (Zoologica Scripta, 2021)
Veneridae is one of the most diverse families of bivalve molluscs. However, their phylogenetic relationships among subfamilies have been debated for years. To explore phylogenetic relationships of Veneridae, we sequenced 13 complete mitochondrial genome sequences from eight subfamilies and compared with available complete mitochondrial genome of other Veneridae taxa (18 previously reported sequences). Phylogenetic analyses using probabilistic methods recovered two highly supported clades. In addition, the protein‐coding gene order revealed a highly conserved pattern among the same subclade lineages. According to our molecular analyses, Tapetinae should be recognized as a valid subfamily, but the genera formed para‐polyphyletic clades. Chioninae was recovered not monophyletic that differs from a previously molecular phylogeny. Furthermore, the reconstructed chronogram calibrated with fossils recovered the Veneridae have originated during the early Permian (about 290 million years ago). Noticeably, programmed frameshift was found in the nad4 gene of Leukoma jedoensis , Anomalodiscus squamosus and Antigona lamellaris and cob gene of L. jedoensis . This is the first time that the presence of the programmed frameshift has been found in the protein‐coding genes of Heterodonta species. Our results improved the phylogenetic resolution within Veneridae, and a more taxonomic sampling analysis of the subfamily Chioninae is supposed to construct.

Mitogenomic phylogeny of Trochoidea (Gastropoda: Vetigastropoda): New insights from increased complete genomes - Erfei Guo; Yi Yang; Lingfeng Kong; Hong Yu; Shikai Liu; Zhanjiang Liu; Qi Li (Zoologica Scripta, 2021)
Increased mitochondrial (mt) genomes can provide more sets of genome‐level characteristics for resolving deeper phylogeny. Limited information with respect to the Trochoidea mitochondrial genome organization is available; besides, monophyly and internal relationships of the superfamily still remain a matter of discussion. To resolve the monophyly and internal phylogenetic controversies of Trochoidea and expand our understanding for mt genomic characteristic evolution among Trochoidea, the phylogenetic trees were reconstructed using 13 newly sequenced complete mt genomes and 35 genomes from GenBank, and both the maximum likelihood and Bayesian inference analyses were highly supported. Vetigastropoda phylogenetic analyses recovered the monophyly of Trochoidea. Trochoidea phylogenetic analyses and genetic distances supported the non‐monophyly of Tegulidae and Tegula , indicating that the taxonomic status of several genera ( Rochia , Tectus and Cittarium ) should be revised and Tegula , Omphalius and Chlorostoma should be placed as a same genus. The close affinity between Tectus virgatus and Rochia was also revealed. Three‐nucleotide insertion in nad1 , nine‐nucleotide insertion and six‐nucleotide deletion in nad5 are detected in Tegulidae, Tectus and Rochia , respectively. Gene orders within Trochoidea are stable, with gene rearrangements exclusive to tRNA genes observed. Homoplasious convergences because of trnT rearrangement display translocation in Turbinidae and reversion in Trochidae and Calliostomatida. For trnE and trnG , we identify 11 arrangement types, suggesting that the gene rearrangement history needs to be further evaluated. Our study emphasizes the importance of mt genomes in resolving phylogenetic relationships within Trochoidea. In addition, the mt genomic characters would contribute new insights into the classification of Trochoidea.

Validation of Housekeeping Genes for Gene Expression Analysis in Iwagaki Oyster (Crassostrea nippona) Under Salinity Stress by Quantitative Real-Time PCR - Jianwen Gong; Qi Li; Hong Yu; Shikai Liu; Lingfeng Kong (Journal of Ocean University of China, 2020)

Seasonal and Spatial Variation of Pelagic Microbial Food Web Structure in a Semi-Enclosed Temperate Bay - Haibo Li; Xue Chen; Michel Denis; Yuan Zhao; Lingfeng Huang; Zengjie Jiang; Wuchang Zhang; Tian Xiao (Frontiers in Marine Science, 2020)

Grazing by microzooplankton and copepods on the microbial food web in spring in the southern Yellow Sea, China - Yuan Zhao; Yi Dong; Haibo Li; Shiquan Lin; Lingfeng Huang; Tian Xiao; Gerald Gregori; Li Zhao; Wuchang Zhang (Marine Life Science & Technology, 2020)
Assessment of microzooplankton and copepods grazing pressure on picoplankton is a key requirement for resolving the microbial food web efficiency. Although microzooplankton grazing on picoplankton has been extensively studied, the impact of microzooplankton on different groups of picoplankton, i.e., heterotrophic bacteria, Synechococcus and picoeukaryotes have rarely been compared. Furthermore, in the very few existing studies there is no consistent evidence of an enhancing or restraining effect of copepods on picoplankton. More studies are needed to improve our understanding of the influence of microzooplankton and copepod on picoplankton. Dilution incubations and copepod addition incubations were performed during a cruise to the southern Yellow Sea on May 16–29, 2007. The bulk grazing of microzooplankton and the calanoid copepod Calanus sinicus on phytoplankton, flagellates and picoplankton was estimated. Stations were divided into either eutrophic or oligotrophic according to the nutrient and biological parameters. Picoplankton comprised a large part of the diet of microzooplankton in the central oligotrophic area, while phytoplankton was the main food of microzooplankton in the coastal eutrophic area. In the central oligotrophic area, microzooplankton preferred grazing on Synechococcus . After copepod addition, ciliate abundance decreased while Synechococcus abundance increased (382%, 64% and 64% at three experimental stations, respectively), indicating strong grazing pressure of microzooplankton on Synechococcus . Our results suggest that Synechococcus might be an essential carbon source the planktonic food web in the oligotrophic waters of southern Yellow Sea.

Mitogenomic phylogeny of the Naticidae (Gastropoda: Littorinimorpha) reveals monophyly of the Polinicinae - Hongyue Liu; Yi Yang; Shao'e Sun; Lingfeng Kong; Qi Li (Zoologica Scripta, 2020)
The Naticidae is a species‐rich family of predatory marine gastropods with substantial interspecific morphological diversity. The classification of the Naticidae has been traditionally based on morphology data, but the phylogenetic relationships within the family are debated due to conflicting molecular results, especially regarding the monophyly of subfamilies Polinicinae and Naticinae. To further resolve the phylogenetic controversies within the Naticidae, we undertake a phylogenetic approach using 14 newly sequenced complete or nearly complete (only lacking a control region) mitochondrial genomes. Both the maximum likelihood and Bayesian inference analyses supported monophyly of the Polinicinae, but paraphyly of the Naticinae due to the placement of the enigmatic genus Notocochlis . The ancestral character reconstruction suggests that the operculum, a character that currently defines the two subfamilies, evolved from an ancestor with a calcareous operculum in the evolutionary history of naticids. In addition, the chronogram estimates that naticids was originated in late Triassic (about 227 million years ago), consistent with previous hypotheses. Our study highlights the importance of using complete mitochondrial genomes while reconstructing phylogenetic relationships within the Naticidae. The evolution scenario of the naticid operculum contributes new insights into the classification of Naticidae.

The geographic and climatic distribution of plant height diversity for 19,000 angiosperms in China - Lingfeng Mao; Nathan G. Swenson; Xinghua Sui; Jinlong Zhang; Shengbin Chen; Jingji Li; Peihao Peng; Guangsheng Zhou; Xinshi Zhang (Biodiversity and Conservation, 2020)

Mass Selection for Growth Improvement in Black Shell Line of Pacific Oyster Crassostrea gigas - Chengxun Xu; Qi Li; Jindou Chong; Shikai Liu; Lingfeng Kong (Journal of Ocean University of China, 2019)

Fertilization, survival and growth of hybrids between Crassostrea gigas and Crassostrea sikamea - Hongqiang Xu; Qi Li; Lingfeng Kong; Hong Yu; Shikai Liu (Fisheries Science, 2019)

Mitogenomic phylogeny of Nassarius (Gastropoda: Neogastropoda) - Yi Yang; Qi Li; Lingfeng Kong; Hong Yu (Zoologica Scripta, 2019)
Nassariids (Family Nassariidae) are a group of marine snails that are distributed worldwide, with their maximum species diversity in tropical regions, particularly the Indo‐Pacific. However, the traditional taxonomy of Nassariidae defined by shell or radula characters is usually inconsistent with little phylogenetic signal. In the present study, the complete mitochondrial (mt) genomes of nine Nassarius species were sequenced and compared with other eight nassariid species previously reported. All nassariid mt genomes showed the same gene order as in most caenogastropods and shared a very similar pattern with respect to genome size, nucleotide composition and AT contents. A deletion of three nucleotides in nad6 gene was detected in Nassarius jacksonianus and Nassarius acuticostus , and this feature also provided implications for nassariid phylogeny. The genetic distance analysis and reconstructed phylogeny revealed a distant relationship between N . jacksonianus or N. acuticostus and other members in Nassarius . The mitogenomic phylogeny recovered the evolutionary relationships within Nassarius with high statistical support. In addition, a chronogram was reconstructed under an uncorrelated relaxed molecular clock, which dated the divergence among main lineages of Nassarius during ~31 MYA.

Initial results of centralized autonomous orbit determination of the new-generation BDS satellites with inter-satellite link measurements - Chengpan Tang; Xiaogong Hu; Shanshi Zhou; Li Liu; Junyang Pan; Liucheng Chen; Rui Guo; Lingfeng Zhu; Guangming Hu; Xiaojie Li; Feng He; Zhiqiao Chang (Journal of Geodesy, 2018)

DNA methylation frequency and epigenetic variability of the Pacific oyster Crassostrea gigas in relation to the gametogenesis - Xin Zhang; Qi Li; Lingfeng Kong; Hong Yu (Fisheries Science, 2018)

The complete mitochondrial genome of Dosinia japonica (Bivalvia: Veneridae) - Changda Lv; Lingfeng Kong; Hong Yu; Qi Li (Conservation Genetics Resources, 2018)

Biochemical Composition and Nutritional Value of Different Shell Color Strains of Pacific Oyster Crassostrea gigas - Yijing Zhu; Qi Li; Hong Yu; Lingfeng Kong (Journal of Ocean University of China, 2018)

Cryptic genetic diversity of Neverita didyma in the coast of China revealed by phylogeographic analysis: implications for management and conservation - Dan Zhao; Lingfeng Kong; Hong Yu; Qi Li (Conservation Genetics, 2018)

Performance of the BDS3 experimental satellite passive hydrogen maser - Ziqian Wu; Shanshi Zhou; Xiaogong Hu; Li Liu; Tao Shuai; Yonghui Xie; Chengpan Tang; Junyang Pan; Lingfeng Zhu; Zhiqiao Chang (GPS Solutions, 2018)

The impact of successive mass selection on population genetic structure in the Pacific oyster (Crassostrea gigas) revealed by microsatellite markers - Jingxiao Zhang; Qi Li; Qingzhi Wang; Rihao Cong; Jianlong Ge; Lingfeng Kong (Aquaculture International, 2018)

Epigenetic variation of wild populations of the Pacific oyster Crassostrea gigas determined by methylation-sensitive amplified polymorphism analysis - Xin Zhang; Qi Li; Lingfeng Kong; Hong Yu (Fisheries Science, 2018)

DNA methylation changes detected by methylation-sensitive amplified polymorphism in the Pacific oyster (Crassostrea gigas) in response to salinity stress - Xin Zhang; Qi Li; Lingfeng Kong; Hong Yu (Genes & Genomics, 2017)

Estimates of Heritability for Growth and Shell Color Traits and Their Genetic Correlations in the Black Shell Strain of Pacific Oyster Crassostrea gigas - Lan Xu; Qi Li; Hong Yu; Lingfeng Kong (Marine Biotechnology, 2017)

Expression and DNA methylation pattern of reproduction-related genes in partially fertile triploid Pacific oysters Crassostrea gigas - Qun Jiang; Qi Li; Hong Yu; Lingfeng Kong (Genes & Genomics, 2017)

Complete mitochondrial genome sequence of Cucullaea labiata (Arcoida: Cucullaeidae) and phylogenetic implications - Yanwei Feng; Qi Li; Hong Yu; Lingfeng Kong (Genes & Genomics, 2017)

Comparison of microsatellites and SNPs for pedigree analysis in the Pacific oyster Crassostrea gigas - Ting Liu; Qi Li; Lingfeng Kong; Hong Yu (Aquaculture International, 2017)

Cryptic diversity of marine gastropod Monodonta labio (Trochidae): did the early Pleistocene glacial isolation and sea surface temperature gradient jointly drive diversification of sister species and/or subspecies in the Northwestern Pacific? - Dan Zhao; Qi Li; Lingfeng Kong; Hong Yu (Marine Ecology, 2017)
Formation of glacial refugia during the Pleistocene climatic oscillations has been put forward to elucidate the diversification of marine organisms in the north‐western Pacific. The marine gastropod Monodonta labio is one of the most common species in the Northwestern Pacific and possibly possesses cryptic diversity. Here, we investigate the phylogeographic pattern of this species to test the potential mechanisms driving its diversification in the Northwestern Pacific. Genetic information for two mitochondrial genes (Cytochrome oxidase subunit I and 16S rDNA) and one nuclear gene (internal transcribed spacer 1) was acquired to detect genetic structuring and to reconstruct the gastropod's phylogenetic history. Our results revealed that M. labio is comprised of five main clades, and divergence time estimates place their cladogenesis as corresponding to the initiation ( c . 2.5 mya) and intensification ( c . 0.9 mya) of large‐scale Northern Hemisphere ice sheets. The early and middle Pleistocene divergence times are consistent with the emergence times of the Dongshan land bridge, which would seperate the ancient East China Sea and the ancient South China Sea forming two potential refugia. In addition, the deep trough in the Qiongzhou Strait would possibly act as another potential refugium with the uplift of the Qiongzhou Strait at mid‐Pleistocene. This study suggests that the current genetic architecture of M. labio is probably correlated with glacial isolation and sea surface temperature gradient. We also put forward the possibility that these factors were probably an important driver for the diversification of sister species or subspecies of other taxa in the Northwestern Pacific.

Relationship between single nucleotide polymorphism of glycogen synthase gene of Pacific oyster Crassostrea gigas and its glycogen content - Siwei Liu; Qi Li; Hong Yu; Lingfeng Kong (Journal of Ocean University of China, 2017)

Genetic variation assessed with microsatellites in mass selection lines of the Pacific oyster (Crassostrea gigas) in China - Xubo Wang; Qi Li; Hong Yu; Lingfeng Kong (Journal of Ocean University of China, 2016)

Gene Co-Expression Network Analysis Reveals the Correlation Patterns Among Genes in Euryhaline Adaptation of Crassostrea gigas - Xuelin Zhao; Hong Yu; Lingfeng Kong; Qi Li (Marine Biotechnology, 2016)

Microsatellite-centromere mapping in Japanese scallop (Patinopecten yessoensis) through half-tetrad analysis in gynogenetic diploid families - Qi Li; Mingjun Qi; Hongtao Nie; Lingfeng Kong; Hong Yu (Journal of Ocean University of China, 2016)

Linkage disequilibrium in wild and cultured populations of Pacific oyster (Crassostrea gigas) - Xiang Guo; Qi Li; Lingfeng Kong; Hong Yu (Journal of Ocean University of China, 2016)

Development of three multiplex PCR primer sets for ark shell (Scapharca broughtonii) and their validation in parentage assignment - Ning Li; Qi Li; Lingfeng Kong; Hong Yu (Journal of Ocean University of China, 2016)

Erratum to: Microsatellite records for volume 7, issue 4 - Rose Komugisha Basiita; J. Henrich Bruggemann; Nianhui Cai; Conchi Cáliz-Campal; Chen Chen; Jiawei Chen; L. Cizek; Pedro J. Cordero; Deborah A. Dawson; Yandong Ding; L. Drag; Anan Duan; et al. (Conservation Genetics Resources, 2016)

Inheritance and Variation of Genomic DNA Methylation in Diploid and Triploid Pacific Oyster (Crassostrea gigas) - Qun Jiang; Qi Li; Hong Yu; Lingfeng Kong (Marine Biotechnology, 2016)

Genetic variation and population structure of the Pacific oyster Crassostrea gigas in the northwestern Pacific inferred from mitochondrial COI sequences - Shuang Li; Qi Li; Hong Yu; Lingfeng Kong; Shikai Liu (Fisheries Science, 2015)

Identification of Single-Locus PCR-Based Markers Linked to Shell Background Color in the Pacific Oyster (Crassostrea gigas) - Jianlong Ge; Qi Li; Hong Yu; Lingfeng Kong (Marine Biotechnology, 2015)

Utility of DNA Barcoding for Tellinoidea: A Comparison of Distance, Coalescent and Character-based Methods on Multiple Genes - Zhenzhen Yu; Qi Li; Lingfeng Kong; Hong Yu (Marine Biotechnology, 2015)

QTL mapping for glycogen content and shell pigmentation in the Pacific oyster Crassostrea gigas using microsatellites and SNPs - Xiaoxiao Zhong; Qi Li; Xiang Guo; Hong Yu; Lingfeng Kong (Aquaculture International, 2014)

Genome-Wide Analysis of Simple Sequence Repeats in Marine Animals—a Comparative Approach - Qun Jiang; Qi Li; Hong Yu; Lingfeng Kong (Marine Biotechnology, 2014)

Expanded Flap to Repair Facial Scar Left by Radiotherapy of Hemangioma - Donghong Zhao; Xinrong Ma; Jiang Li; Lingfeng Zhang; Baozhen Zhu (Cell Biochemistry and Biophysics, 2014)

Molecular cloning and differential expression in tissues of a tyrosinase gene in the Pacific oyster Crassostrea gigas - Xue Yu; Hong Yu; Lingfeng Kong; Fengguang Guo; Guan Zhu; Qi Li (Molecular Biology Reports, 2014)

The effect of chemical cues on the settlement of sea cucumber (Apostichopus japonicus) larvae - Xiujun Sun; Qi Li; Hong Yu; Lingfeng Kong (Journal of Ocean University of China, 2014)

Additional lines of evidence provide new insights into species diversity of the Paphia subgenus Protapes (Mollusca, Bivalvia, Veneridae) in seas of south China - Jun Chen; Qi Li; Lingfeng Kong; Xue Yu (Marine Biodiversity, 2014)

Comparative phylogeography in marginal seas of the northwestern Pacific - Gang Ni; QI Li; Lingfeng Kong; Hong Yu (Molecular Ecology, 2014)
The maturation of marine phylogeography depends on integration of comparative information across different regions globally. The northwestern Pacific, characterized by unique tectonic setting, however, is still underrepresented. This study seeks to highlight its phylogeographical history based on the available population data, focusing on three seas: the East China Sea ( ECS ), the South China Sea ( SCS ) and the Sea of Japan ( SOJ ). We first conducted a literature survey to evaluate current research efforts and then reanalysed the population structure, historical demography and genealogy for two selections of studies (namely ‘the ECS category’ and ‘the multiple‐sea category’) to elucidate the evolutionary processes within and across the seas, respectively. For the ECS category, the meta‐analyses revealed most studies displayed a shallow phylogeny, indicating a single origin from the sea. Significant population structure was commonplace, particularly in molluck and crustacean studies, with proportions of 89% and 80%, respectively. Nearly all studies selected showed signals of population expansion: the times estimated were closely linked to a period of ~120–140 Kya rather than the last glacial maximum. For the latter category, divergent intraspecific lineages appeared among seas and overlapped in the adjacent regions, a pattern implying each sea had served as an independent refugium during glaciations. The genetic splits, however, were estimated to arise from separate events dating from late Miocene to middle Pleistocene. As phylogeography is still in its infancy in the region, more effort is needed to test and complement the general rules abstracted here. Finally, challenges and prospects were discussed to accelerate further research.

Mitogenome evidence for the existence of cryptic species in Coelomactra antiquata - Yang Yuan; Lingfeng Kong; Qi Li (Genes & Genomics, 2013)

Isolation and characterization of 23 microsatellite loci in the veined rapa whelk (Rapana venosa) - Junting An; Hong Yu; Ruihai Yu; Lingfeng Kong; Qi Li (Conservation Genetics Resources, 2013)

Reproductive cycle and seasonal variations in lipid content and fatty acid composition in gonad of the cockle Fulvia mutica in relation to temperature and food - Wenguang Liu; Qi Li; Lingfeng Kong (Journal of Ocean University of China, 2013)

Isolation and characterization of 18 polymorphic microsatellite loci in the surf clam (Mactra veneriformis) - Hongtao Nie; Ning Li; Lingfeng Kong; Qi Li (Conservation Genetics Resources, 2013)

Isolation and characterization of 14 microsatellite loci in Macridiscus semicancellata (Koch in Philippi, 1843) - Xinyu Liu; Lingfeng Kong; Hong Yu; Qi Li (Conservation Genetics Resources, 2013)

Genetic Positioning of Centromeres through Half-Tetrad Analysis in Gynogenetic Diploid Families of the Zhikong Scallop (Chlamys farreri) - Hongtao Nie; Qi Li; Xuelin Zhao; Lingfeng Kong (Marine Biotechnology, 2013)

Response to selection for fast growth in the second generation of Pacific oyster (Crassostrea gigas) - Qingzhi Wang; Qi Li; Lingfeng Kong; Ruihai Yu (Journal of Ocean University of China, 2012)

Inhibitory effect of Salicornia europaea on the marine alga Skeletonema costatum - Dan Jiang; LingFeng Huang; YongQing Lin; LingLing Nie; SuLian Lv; TingYun Kuang; YinXin Li (Science China Life Sciences, 2012)

Isolation and characterization of 20 microsatellite loci in Neverita didyma (Röding 1798) - Ning Li; Qi Li; Minyu Jin; Lingfeng Kong; Hong Yu (Conservation Genetics Resources, 2012)

The complete mitochondrial genome of the grand jackknife clam, Solen grandis (Bivalvia: Solenidae): a novel gene order and unusual non-coding region - Yang Yuan; Qi Li; Lingfeng Kong; Hong Yu (Molecular Biology Reports, 2012)

Multigene Barcoding and Phylogeny of Geographically Widespread Muricids (Gastropoda: Neogastropoda) Along the Coast of China - Shanmei Zou; Qi Li; Lingfeng Kong (Marine Biotechnology, 2012)

Multiparameter cluster analysis of seasonal variation of water masses in the eastern Beibu Gulf - Shengli Chen; Yan Li; Jianyu Hu; Airong Zheng; Lingfeng Huang; Yuanshao Lin (Journal of Oceanography, 2011)

Selection response and realized heritability for growth in three stocks of the Pacific oyster Crassostrea gigas - Qi Li; Qingzhi Wang; Shikai Liu; Lingfeng Kong (Fisheries Science, 2011)

Identification and characterization of 43 microsatellite markers derived from expressed sequence tags of the sea cucumber (Apostichopus japonicus) - Qun Jiang; Qi Li; Hong Yu; Lingfeng Kong (Journal of Ocean University of China, 2011)

Gametogenic cycle and biochemical composition of the clam Mactra chinensis (Mollusca: Bivalvia): Implications for aquaculture and wild stock management - Qi Li; Lin Yang; Qiaozhen Ke; Lingfeng Kong (Marine Biology Research, 2011)

Molecular phylogeny of venus clams (Mollusca, Bivalvia, Veneridae) with emphasis on the systematic position of taxa along the coast of mainland China - Jun Chen; Qi Li; Lingfeng Kong; Xiaodong Zheng (Zoologica Scripta, 2011)
Chen, J., Li, Q., Kong, L. & Zheng, X. (2011). Molecular phylogeny of venus clams (Mollusca, Bivalvia, Veneridae) with emphasis on the systematic position of taxa along the coast of mainland China. — Zoologica Scripta , 40 , 260–271. Veneridae is the most richly speciose family of heterodont bivalves with high ecological and economic value. Attention to the Veneridae systematics has been raised since traditional conchology‐based ideas on relationships among the venerids were challenged by recent studies using molecular makers and other new approaches and methods. Herein, DNA sequence information from fragments of two mitochondrial genes (COI and 16S) and one nuclear protein‐coding gene (H3) for 135 taxa (128 venerids, five nonvenerid veneroids and two other outgroups) are used to reconstruct the phylogenetic relationships of venus clams under maximum parsimony, maximum likelihood and Bayesian inference approaches. According to our molecular results, the traditional Veneridae is not recovered as monophyletic and most of the nominal subfamilies and genera formed para‐polyphyletic clades. The findings indicate that the current venerid classification cannot validly reflect a natural subdivision. In the present study, the classification of taxa along the coast of mainland China within this family are also revised based on their phylogenetic position and morphological characters. The synonymization of chionine genus Placamen with Clausinella is rejected. Chionine subgenera Anomalodiscus and Cryptonema are given full generic rank again and incorporated into Venerinae and Tapetinae, respectively. Tapetine Marcia hiantina , M. japonica and M. marmorata were distantly related to Katelysia spp., so assigning those three species into the genus Katelysia by some malacologists is rejected herein. Our results also evidence that the synonymization of the genus Tigammona and Periglypta might be inappropriate.

DNA barcoding and phylogenetic analysis of Pectinidae (Mollusca: Bivalvia) based on mitochondrial COI and 16S rRNA genes - Yanwei Feng; Qi Li; Lingfeng Kong; Xiaodong Zheng (Molecular Biology Reports, 2011)

Effect of starvation on biochemical composition and gametogenesis in the Pacific oyster Crassostrea gigas - Wenguang Liu; Qi Li; Fengxiang Gao; Lingfeng Kong (Fisheries Science, 2010)

Genetic variation and differentiation in wide ranging populations of razor clam (Sinonovacula constricta) inferred from AFLP markers - Jingbo Wang; Qi Li; Lingfeng Kong (Journal of Ocean University of China, 2010)

Isolation and characterization of 19 microsatellite markers from the Chinese surf clam (Mactra chinensis) - Lehai Ni; Qi Li; Lingfeng Kong (Conservation Genetics Resources, 2010)

Seasonal changes in reproductive activity and biochemical composition of the razor clam Sinonovacula constricta (Lamarck 1818) - Hongwei Yan; Qi Li; Wenguang Liu; Ruihai Yu; Lingfeng Kong (Marine Biology Research, 2010)

Genetic diversity and population structure of the golden cuttlefish, Sepia esculenta (Cephalopoda: Sepiidae) indicated by microsatellite DNA variations - Xiaodong Zheng; Minoru Ikeda; Lingfeng Kong; Xiangzhi Lin; Qi Li; Nobuhiko Taniguchi (Marine Ecology, 2009)
The golden cuttlefish, Sepia esculenta Hoyle, 1885 (Cephalopoda: Sepiidae) is a valuable and important fishery resource for China, Japan and Korea. This fishery has experienced severe population decline largely due to overexploitation in past decades. To provide guidelines for fisheries management, we estimated genetic diversity and population structure across four locations along the coast of Japan and one location in China (a total 281 individuals) using nine microsatellite DNA loci. Sepia esculenta showed high genetic variability with mean allele richness ranging from 15.8 to 21.4, and mean heterozygosity from 0.80 to 0.90. Weak but significant genetic differentiation was present and the F ST value was 0.020 across all five populations. The useful information obtained in this study will offer insights into how to fine‐tune conservation and fishery management measures for this species and resource in the future.

Genetic and morphological variation in the venus clam Cyclina sinensis along the coast of China - Yuming Zhao; Qi Li; Lingfeng Kong; Yuze Mao (Hydrobiologia, 2009)

Characterization of expressed sequence tag-derived single-nucleotide polymorphisms in the bay scallop Argopecten irradians irradians - Ronghua Li; Qi Li; Lingfeng Kong (Fisheries Science, 2009)

Genetic evidence for the existence of cryptic species in an endangered clam Coelomactra antiquata - Lingfeng Kong; Qi Li (Marine Biology, 2009)

Estradiol‐17β and testosterone levels in the cockle Fulvia mutica during the annual reproductive cycle - Wenguang Liu; Qi Li; Lingfeng Kong (New Zealand Journal of Marine and Freshwater Research, 2008)
In this study, we investigated seasonal variations in the concentrations of estradiol‐17β (E 2 ) and testosterone (T) in the gonad of the cockle Fulvia mutica from March 2004 to February 2005 in relation to the reproductive cycle. Histological data showed that F. mutica is a hermaphrodite bivalve species, and gametogenesis took place during winter‐spring (November‐April) and spawning occurred in summer (May‐June) when water temperature was higher. E 2 and T concentrations were measured by enzyme‐linked immunosorbent assay (ELISA). E 2 concentrations varied between 7.27 and 32.63 pg/g wet weight and T concentrations ranged from 22.83 to 77.15 pg/g wet weight throughout the year. Both steroids exhibited a similar annual pattern that correlated with the reproductive cycle. The two peaks of E 2 and T concentrations in November and May‐June occurred at critical moments of the F mutica reproductive cycle: the onsets of gametogenesis and of the spawning period. E 2 andT concentrations were low during the non‐reproductive period extending from July to October. These results suggest that E 2 and T could play a role as endogenous modulators in the reproductive cycle of F. mutica .

Genetic Structure of the Veined Rapa Whelk (Rapana venosa) Populations Along the Coast of China - Jianmin Yang; Qi Li; Lingfeng Kong; Xiaodong Zheng; Rucai Wang (Biochemical Genetics, 2008)

Genetic diversity and divergence among clam Cyclina sinensis populations assessed using amplified fragment length polymorphism - Yuming Zhao; Qi Li; Lingfeng Kong; Zhenmin Bao; Rucai Wang (Fisheries Science, 2007)

Seasonal variation of the glycogen enzyme activity in diploid and triploid Pacific oyster gonad during sexual maturation - Lingfeng Kong; Zhaoping Wang; Ruihai Yu; Qi Li; Rucai Wang (Journal of Ocean University of China, 2007)